“NÓS SOMOS UMA FAMÍLIA”: AS VIVÊNCIAS DE PROFESSORES DA EDUCAÇÃO BÁSICA À LUZ DA PSICODINÂMICA DO TRABALHO - Reinaldo, Felipe Alves (2020)
In the light of the Psychodinamics of Work, this study aims to analyze the cooperation in face of impasses and the constraints of the organization of teaching work in the municipal public schools of Sobral, a city in the countryside of the state of Ceará.